Penatalaksanaan Hasil Pemeriksaan Crossmatch Mixed Field pada Pasien Pra-Transfusi Darah di RSUD Prof. Dr. Margono Soekarjo: Studi Kasus - Meisi Feti Riskiana Meisi; Risma Cahyani; Aisah Putri Umahar; Dilla Putri Oktafiani; Riska Almaidah Putri (LPPM Universitas Abdurrab, 2026)
Crossmatching is a critical pre-transfusion test to ensure compatibility between donor and recipient blood. This case report describes crossmatch findings in a 47-year-old male with O Rh-positive blood type and aplastic anemia who required packed red blood cells (PRBC). Using the gel test method, mixed-field reactions were observed in major tests 1 and 2, while the minor test was negative; the autocontrol was positive and the direct Coombs test was negative, suggesting partial incompatibility. Repeat ABO/Rh verification, replacement of the donor unit, and red-cell washing produced consistent results. After clinical assessment and discussion with the attending physician, transfusion proceeded with leukodepleted PRBC to reduce the risk of transfusion reactions. This case highlights the need for rigorous interpretation of crossmatch results and close collaboration between laboratory staff and clinicians in transfusion decision-making.